ANALYSIS OF POLITENESS STRATEGIES IN COMMAND USED BY MAIN CHARACTERS IN MOVIES ENTITLED “FACING THE GIANTS”, “DANGEROUS MINDS”, AND “THE RON CLARK STORY” - Eftanastarini, Indah (Jurnal Pedagogy, 2016)
In communication, the speakers should be polite toward the hearers by considering their social level, age, situation, and condition. The current study focused on the use of politeness strategies, especially in command. The aims of the study are to identify the types of sentence in command, the applied of politeness strategies, and to investigate the factors that influence the main characters in applying politeness strategies in command. The data were politeness utterances in command used by main character in 3 drama movies: “Facing the Giants”, “Dangerous Minds”, and “The Ron Clark Story”. The data were analyzed using politeness strategies purposed by Brown and Levinson (1987). The results of this study shown that there are 2 forms of command: declarative sentence and imperative sentence. The characters applied 2 types of politeness strategy in giving command: bald on record (24 data) and positive politeness (4 data). The factors that influenced the main characters in applying politeness strategies in command were the main characters, as the speakers, have higher status than the hearers, the size of imposition between the speakers and the hearers were small, and the situation were urgent and emergency in which the speakers and the hearers involved.